Project Management Competences in the light of Economy 4.0 - Malgorzata ZAKRZEWSKA; Malgorzata KOSALA; Szymon JAROSZ (Communications of International Proceedings, 2021)
The article deals with the broadly understood subject of competences of project managers in the era of Revolution 4.0 and constant social, technical and economic changes. The article refers to the guidelines for individual competences proposed in 2015 by the International Project Management Association. The authors present the results of empirical research on the level of competences of individual project managers in the context of the following characteristics: sector, role and experience.
Keywords: Project Management; Competences; Economy 4.0